2013
DOI: 10.1016/j.bpj.2013.02.029
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sterols on Amphotericin B Self-Aggregation in a Lipid Bilayer as Revealed by Free Energy Simulations

Abstract: Amphotericin B (AmB) is an effective but toxic antifungal drug, known to increase the permeability of the cell membrane, presumably by assembling into transmembrane pores in a sterol-dependent manner. The aggregation of AmB molecules in a phospholipid bilayer is, thus, crucial for the drug's activity. To provide an insight into the molecular nature of this process, here, we report an atomistic molecular dynamics simulation study of AmB head-to-head dimerization in a phospholipid bilayer, a possible early stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 65 publications
1
19
1
Order By: Relevance
“…Furthermore, while there was a substantial reduction in renal toxicity for mAmB versus Fungizone ® , there was not change in the minimal inhibitory concentration against Candida albicans for mAmB versus Fungizone ® (data not shown). This is consistent with the aggregation state hypothesis and many in vitro studies that have shown that monomeric AmB is selectively toxic for fungal cells, whereas aggregated species of AmB form damaging pores in fungal and mammalian cell membranes [6, 13]. …”
Section: Resultssupporting
confidence: 89%
“…Furthermore, while there was a substantial reduction in renal toxicity for mAmB versus Fungizone ® , there was not change in the minimal inhibitory concentration against Candida albicans for mAmB versus Fungizone ® (data not shown). This is consistent with the aggregation state hypothesis and many in vitro studies that have shown that monomeric AmB is selectively toxic for fungal cells, whereas aggregated species of AmB form damaging pores in fungal and mammalian cell membranes [6, 13]. …”
Section: Resultssupporting
confidence: 89%
“…Ergosterol has been proposed as a target molecule in the medical treatment of fungal infections, following mainly two routes: (i) the inhibition of the biosynthesis of ergosterol, as in the case of ketoconazole and clotrimazole drugs action, and (ii) direct interaction, as in the case of amphotericin B, where two reaction mechanisms have been proposed . The first mechanism proposed for direct interaction of ergosterol with amphotericin B has been widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…The AmB has fungicidal effects and its efficacy is based on the drug capacity to link with ergosterol, and the main sterol constituting the cell membrane. It disturbs osmotic equilibrium in the cell membrane, increases the permeability of the cell membrane and consequently results in the subsidence of the cell ingredients and the death of fungal cells (7)(8)(9).…”
Section: Polyenes (Amphotericin B)mentioning
confidence: 99%